Investor’s behavior and stock investment decision in batam city - Jusky Novianto; Robin Robin (AKUNTABEL, 2021)
This study aims to analyze the influence of investor’s behavior on investment decisions in stock investing in Batam City. The investor’s behavior consists of heuristic theory, herding behavior, and prospect theory. The heuristic theory used in this study consists of representativeness, overconfidence, availability, and anchoring. Whereas prospect theory consists of loss aversion, regret aversion, and mental accounting. This study used a purposive sampling method, which is the sample is selected by the criteria that are the investor who has a stock investment in Batam. The total sample is 200 respondents. The research method is multiple regression with SPSS software. The results show that there are only three behaviors from the heuristic theory that have a significant effect on investment decisions, namely representativeness, availability, and anchoring. Meanwhile, overconfidence does not have a significant effect. Herding behavior does not have a significant effect. Meanwhile, prospect theory is only mental accounting behavior that has a significant effect and loss aversion and regret aversion have no significant effect.